A Note of Appreciation for Adam Podgórecki Who Alerted the Oxford Centre for Socio-Legal Studies Many Years Ago to the Importance of the Rule of Law, Thus Preparing Us for Recent Challenges - Maclean, Mavis (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2024)
This article records thanks to Adam Podgórecki for introducing discussion of the rule of law on his visit to the Oxford Centre for Socio-Legal Studies fifty years ago, and for stimulating use of the concept during the recent period of 14 years of Tory government in the UK, which ended in July 2024.